2017
DOI: 10.1038/srep44444
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-3 receptors expressed in Nkx2.1(+ve) neurons are sufficient for controlling appetitive responses to hypocaloric conditioning

Abstract: Melanocortin-3 receptors (MC3R) have a contextual role in appetite control that is amplified with hypocaloric conditioning. C57BL/6J (B6) mice subjected to hypocaloric feeding schedules (HFS) exhibit compulsive behavioral responses involving food anticipatory activity (FAA) and caloric loading following food access. These homeostatic responses to calorie-poor environs are attenuated in B6 mice in which Mc3r transcription is suppressed by a lox-stop-lox sequence in the 5’UTR (Mc3rTB/TB). Here, we report that op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 64 publications
2
28
0
2
Order By: Relevance
“…The response of NAG neurons to hypocaloric conditioning is restored in LoxTB Mc3r mice in which hypothalamic expression was rescued using Nkx2.1-Cre (Girardet et al, 2017). This study also observed that restoring FAA in LoxTB Mc3r mice is independent of improvements in adiposity.…”
Section: Is There a Role For Mc3rs In Appetite Regulation?mentioning
confidence: 99%
“…The response of NAG neurons to hypocaloric conditioning is restored in LoxTB Mc3r mice in which hypothalamic expression was rescued using Nkx2.1-Cre (Girardet et al, 2017). This study also observed that restoring FAA in LoxTB Mc3r mice is independent of improvements in adiposity.…”
Section: Is There a Role For Mc3rs In Appetite Regulation?mentioning
confidence: 99%
“…In summary, the current results indicate that MC3R signaling in AgRP +ve neurons appears to have an inhibitory role in regulating feeding behavior. When compared with previous studies using this model (2,(29)(30)(31), there appears to be functional divergence between MC3Rs expressed on first-order and second-order neurons of the central nervous melanocortin system. MC3Rs expressed on first-order AgRP +ve neurons are inhibitory.…”
Section: Discussionmentioning
confidence: 71%
“…Ventral tegmental area MC3Rs support the expression of feeding-related motivational responses during situations of energy deficit (29). MC3R signaling in Nkx2.1 +ve neurons in the hypothalamus also supports behavioral adaptation to energy deficit (30). MC3R signaling in the nervous system thus appears to be predominantly orexigenic, particularly during situations of energy deficit.…”
Section: Discussionmentioning
confidence: 97%
“…However, exactly where and how MC3Rs affects metabolic control to alter nutrient partitioning is not known. Interestingly, the impact of Mc3r deficiency on feeding behavior when food is freely available is very minor; however, responses to hypocaloric conditioning are compromised featuring partial insulin resistance and enhanced lipogenesis [112]- [114]. Apart from metabolic features, Mc3r null mice develop other phenotypes such as high susceptibility to salt-sensitive hypertension [115] and, due to expression of MC3R outside the brain, increased immune response resulting in a complex phenotype (reviewed in [116]).…”
Section: The Role Of Mc3r In Metabolic Regulationmentioning
confidence: 99%